Exploring the renewal of pedagogy: problem-based learning as a space for young peoples’ educational citizenship (Educação e Pesquisa, 2023)
This article explores how problem-based learning (PBL) can contribute to renewing pedagogy by placing young people at the center of the pedagogical relationship of knowledge construction, and enabling them to realize their rights. The starting point is the concern about the lack of space for listening to young people in different educational contexts and the recognition of the members of this social group as subjects of the construction of their citizenship. Their voices are crossed with those of teachers and researchers. It is argued that PBL can create space for the young people to enact “educational citizenship”. Grounded on the renewal of pedagogy, PBL constitutes a participatory method based on initiative, decision-making and supportive relationships. Within the scope of the EduTransfer project, and in dialogue with educational citizenship, PBL is seen as a curriculum development process, and a teaching-learning theory and method that can create space for realizing this citizenship. PBL gains a place as a strategy for educational institutions to ensure rights. It is these aspects that we focus on throughout the article, giving rise to a reflection on the different moments of this educational strategy. After focusing on methodological and procedural options, we bring together the voices of teachers, young people and researchers to explore PBL in action. While we assert the value of this approach, we also recognize limits to its implementation.